Research methods in intercultural communication : a practical guide - Hua, Zhu, 1970- (Malden, MA : Wiley-Blackwell, 2016)
'The focus is on the process of interaction and what the participants achieve out of the experience in terms of new values, identities and practices'--
Further Reading and Resources9 How to Work with Research Participants: The Researcher's Role; Introduction; Critical Reflexivity and Process Interculturality; Co-constructing Research: Beyond'Repressed Reflexivity'?; An example; Conclusion; Key Terms; References; Further Reading and Resources; 10 How to Develop a Research Proposal; Getting Started; The Research Proposal; Ethics and Human Relations; Conclusion; Key Terms; References; Further Reading and Resources; Part III Methods; 11 Questionnaires and Surveys; What this Method is About; Why this Method and Why Not; How to Do It
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Intercultural communication -- Research; Intercultural communication -- Methodology; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; Intercultural communication -- Methodology; Intercultural communication -- Research; Electronic books